Expression of glycoside hydrolases in Aspergillus niger - Raulo, Roxane (2016)
Enzymes from filamentous fungi have a key role in degradation of the most abundant biopolymers found in nature, cellulose and hemicelluloses. For this reason, these enzymes are of great interest in the industrial conversion of lignocellulosic substrates into biofuels. The production of plant cell wall degrading enzymes is regulated mainly at the transcriptional level in filamentous fungi but little is known about the signalling pathways and transcription factors (TFs) involved in this regulation in Aspergillus niger. RNA-sequencing analysis has been previously carried out to investigate the transcriptional changes that occur when A. niger is transferred from the simple carbon source glucose onto the complex lignocellulosic biomass wheat straw. This has highlighted the up-regulation in transcript level of genes encoding some glycosyl hydrolase (GH) enzymes as well as hydrophobic surface interacting proteins (HSIPs) that may be involved in the interface between lignocellulosic biomass and A. niger. Genes encoding the key TFs XlnR, ClrA and ClrB were deleted from A. niger and the resulting strains were assessed for growth on glucose and wheat straw, transcription of genes encoding glycosyl hydrolases and saccharification activity. Growth of all mutant strains, based in straw on measurement of pH and assay of glucosamine, was impaired in relation to the wild-type (WT) strain although deletion of clrA had less effect than deletion of xlnR or clrB. Release of sugars from wheat straw was also lowered when culture filtrates from TF deletion strains were compared with WT culture filtrates. Transcript levels of cbhA, bglB, eglC and xynA were measured in all strains in glucose and wheat straw media in batch culture with and without pH control. Transcript levels from cbhA, bglB and eglC were lowered in all mutant strains compared to WT although the impact of deleting clrA was not pronounced with expression of eglC and had no effect on xynA. The impact on transcription was not related to changes in pH. In addition to impaired growth on wheat straw, the ΔxlnR strain was sensitive to oxidative stress and displayed cell wall defects in the glucose condition suggesting additional roles for XlnR. Phosphorylation is a key reversible modification that regulates protein function, subcellular localization, complex formation, activation of TFs and cell signalling pathways. A phosphoproteomic study was carried out on both the WT and the ΔxlnR deletion strains of A. niger in order to identify key regulators of the signalling pathways involved in the breakdown of a lignocellulosic substrate, wheat straw. The analysis consisted of comparing the phosphoproteome profiles of the strains when grown in glucose with the phosphoproteome profile of the same strains when exposed to wheat straw for 6h, 12h and 24h. The results suggested a difference in the phosphoproteome profiles of the two strains when exposed to both glucose and wheat straw. These data may provide new information on the importance of XlnR in the regulation of expression of GHs but also in controlling the environment to which A. niger is exposed depending on the nutrient availability. To investigate the role of HSIPs in the induction of A. niger response to wheat straw, single gene deletion strains for hfbD, hyp1 and hsbA as well as the double deletion strain for hfbD and hyp1 have been constructed. The expression of some genes encoding GH enzymes was then followed in these strains using qRT-PCR. The results showed that the transcript levels of the GH genes studied were lowered in the HSIPs deletion strains when compared to the wild-type strain, when the cultures were transferred from glucose medium to wheat straw. These results suggest that HSIPs may have a role in the utilisation of lignocellulosic biomass in A. niger. The precise nature of such a role as well as the characterisation of new TFs, such as ClrB, provides new areas of improvement for industrial processes for production of second generation biofuels.